The socioeconomic variables influence in the alpha-tocopherol concentration of the maternal serum - Karla Danielly S. Ribeiro; Luana Weigert; Talita Andrade; Amanda Lima; Jeane Medeiros; Mayara Lima; Danielle Bezerra; Mônica Osório; Roberto Domenstein
Abstract Objectives: To evaluate the influence of the socioeconomic factors on the alpha-tocopherol concentration in maternal serum. Methods: a retrospective, observational, cross-sectional study with the participation of 103 adult parturient volunteers attended at Hospital Universitário Ana Bezerra (Ana Bezerra University Hospital) in Santa Cruz - Rio Grande do Norte. 5.0 mL of blood was collected from each participant in fasting before the delivery to extract alpha-tocopherol of the serum. Socioeconomic and demographic information were obtained by a previously structured questionnaire. Alpha-tocopherol serum was determined by a High-Performance Chromatography Liquid (Cromatografia Líquida de Alta Eficiência (CLAE). Results: The average concentration of alpha-tocopherol in the serum was 1281.4 (594.8) µg/dL, and 6% of the women presented vitamin E deficiency (DVE). Most pregnant women aged between 18 and 24 years (59%), marital status was married or consensual marriage (77%), elementary schooling complete (34%), low family income (74%) and living in the urban area (73%). No significant differences were found in the alpha-tocopherol concentration according to socioeconomic characteristics and none of the studied factors were associated to the presence of DVE ( p >0.05). Conclusions: The maternal social characteristics were not determinants for the alpha-tocopherol serum and DVE. Further investigations should be carried out during lactation to assess which factors may be involved in the presence of this deficiency.